2006
DOI: 10.1590/s0103-84782006000500014
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid alfentanil, butorphanol, and morphine concentrations following caudal epidural administration in horses

Abstract: This study was conducted with the objective of determining the plasma and cerebrospinal fluid (CSF 5, 10, 20, 30, 40, 50, 60 and 120

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…So far, no pharmacokinetic studies about morphine and its metabolites after repeated epidural administration have been reported in horses. Natalini (2006) [13] investigated the plasmatic concentration of morphine after a single epidural injection of 0.1 mg/kg in horses and found maximum plasmatic concentration of 90 ng/ ml at 120 min post-injection; no clinical variables were reported.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no pharmacokinetic studies about morphine and its metabolites after repeated epidural administration have been reported in horses. Natalini (2006) [13] investigated the plasmatic concentration of morphine after a single epidural injection of 0.1 mg/kg in horses and found maximum plasmatic concentration of 90 ng/ ml at 120 min post-injection; no clinical variables were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the occurrence of adverse side effects, like increased gastrointestinal transit time, were not studied systematically in the present study, no apparent adverse side effects were observed after any of the two treatments. Throughout the entire study period, the serum concentrations of morphine after IA administration (0.05 mg kg −1 ) were lower than those of 0.1 mg kg −1 reported both after epidural (Natalini 2006) and after IV (Combie et al. 1983) administration of morphine.…”
Section: Discussionmentioning
confidence: 99%
“…One of the inducing factors of postoperative nausea and vomiting is the use of opioids in the process of anesthesia. Basbaum and Fields and Watcha and White [46] found that the main analgesic mechanism of fentanyl was that opioid receptors distributed in the central nervous system are blocked. Hence, pain signals could not be transmitted upwards.…”
Section: Discussionmentioning
confidence: 99%
“…This is a new analgesic technique that has been widely used in recent years. [6] Opioids are the main drugs for clinical analgesia, and fentanyl and sufentanil have been widely used in postoperative analgesia. However, opioids cause adverse reactions such as nausea, vomiting, dizziness, sleepiness, and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%